2020
DOI: 10.3390/polym12092113
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress and Development Demand of Nanocellulose Reinforced Polymer Composites

Abstract: Nanocellulose is a type of nanomaterial with high strength, high specific surface area and high surface energy. Additionally, it is nontoxic, harmless, biocompatible and environmentally friendly and can be extracted from biomass resources. The surface groups of cellulose show high surface energy and binding activity on the nanoscale and can be modified by using various methods. Because nanocellulose has a high elastic modulus, rigidity and a low thermal expansion coefficient, it is an excellent material for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 99 publications
(127 reference statements)
0
37
0
Order By: Relevance
“…Poor dispersion of tactoids reduces the efficiency of the B filler in reinforcing the matrix. C can better reinforce the TPS due to its fibrous-like particles that can transfer the load more efficiently [ 34 ]. However, when used as hybrid filler with the B, C cannot be added in more than 1 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…Poor dispersion of tactoids reduces the efficiency of the B filler in reinforcing the matrix. C can better reinforce the TPS due to its fibrous-like particles that can transfer the load more efficiently [ 34 ]. However, when used as hybrid filler with the B, C cannot be added in more than 1 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, nanocelluloses are not cost-effective compared to their alternatives due to low production capacities. Shen et al (2020) discussed the factors inhibiting the commercialization of nanocellulose reinforced polymer composites. Authors reported that pretreatment costs and low production capacities associated with nanocelluloses resulted in substantially higher production costs compared to the alternatives such as nanomontmorillonite and nanosilica.…”
Section: Techno-economic Assessmentmentioning
confidence: 99%
“…through a β-1,4-glycosidic linkage (Thakur et al, 2022;Thakur & Voicu, 2016). Each monomer residue contains hydroxyl groups that form extensive intra-and inter-molecular hydrogen bonds with adjacent glucose residues in the same and nearby chains (Barhoum et al, 2020;Li et al, 2018;Moon et al, 2011;Shen et al, 2020). The mechanical stability of material plays an important role which could be explored in various applications (Verma et al, 2018).…”
Section: Review Articlementioning
confidence: 99%